2022
DOI: 10.1096/fba.2021-00131
|View full text |Cite
|
Sign up to set email alerts
|

The roles of HMGB1‐produced DNA gaps in DNA protection and aging biomarker reversal

Abstract: The endogenous DNA damage triggering an aging progression in the elderly is prevented in the youth, probably by naturally occurring DNA gaps. DecreasedThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…The formation of DNA gaps is one of the cellular mechanisms that maintains DNA integrity. As a result, the role of youth-DNA-gaps is similar to that of gaps that remain between successive rails in a railway track, that is, relieving torsion force to prevent damage 33 . We previously demonstrated that reducing the DNA gap resulted in DNA shearing 37 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of DNA gaps is one of the cellular mechanisms that maintains DNA integrity. As a result, the role of youth-DNA-gaps is similar to that of gaps that remain between successive rails in a railway track, that is, relieving torsion force to prevent damage 33 . We previously demonstrated that reducing the DNA gap resulted in DNA shearing 37 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that reducing the DNA gap resulted in DNA shearing 37 . Moreover, introducing new Box A-produced DNA gaps increased DNA resistance to radiation-induced DNA breaks, rejuvenated senescent cells, and rejuvenated both naturally and d-galactose-induced aging rats 33 . Two types of DNA breaks occur in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alu methylation, a specific form of DNA methylation, has been shown to play a role in minimizing the accumulation of endogenous DNA damage 30 . This effect is achieved by reducing the torsional force on the DNA double helix through naturally occurring hypermethylated DNA gaps 31–35 . Previous studies have indicated that type 2 DM patients accumulated DNA damage, 36–38 leading to genomic instability and cellular senescence 39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…30 This effect is achieved by reducing the torsional force on the DNA double helix through naturally occurring hypermethylated DNA gaps. [31][32][33][34][35] Previous studies have indicated that type 2 DM patients…”
mentioning
confidence: 99%